Uma abordagem histórica dos padrões de rendimento mínimo em Portugal - José António Pereirinha; Francisco Branco (Ler História, 2013)
This paper presents an interpretive analysis of the history of the minimum social in Portugal. We intend to rebuild the historical journey of the evolution of minimum income standards, identifying and contextualizing the milestones that influenced their evolution. This analysis is part of a research project that intends, through a consensual approach of standard budgets, to determine the value of adequate minimum income in Portugal and make a comparison with the values of minimum social standards that constitute a reference for setting values for the minimum wage and social benefits.